From curiosity to wonder in religious education - Corcoran, Paul (Journal of Religious Education, 2024)
This study argues that religious education is uniquely positioned to resist and transcend contemporary dialectics of wonder that serve to diminish, commodify, or instrumentalize the place of wonder in society today. Wonder is traditionally characterized by a sense of importance that accompanies our encounters with mystery. In a world less comfortable with interiority and less willing to accept the sense of ignorance true wonder presupposes, the contemplative element of wonder has largely evaporated, to be replaced by a more fleeting (Schinkel in Stud Philos Educ 39(5):479–492, 2019, 481) and less challenging ‘curiosity’. Curiosity favours mastery over mystery; it elides the puzzlement or contemplation inherent in traditional understandings of wonder. In pedagogical settings, curiosity is increasingly advanced at a catalyst that motivates and directs the inquiry of the learner. However, educational literature continues to note a worrying absence of any kind of wonder in classrooms today (Jirout et al. in Front Psychol 13:875161, 2022. https://doi.org/10.3389/fpsyg.2022.875161). This study will suggest that the advancement of wonder as curiosity in education only reinforces the very sense of apathy it is designed to counteract in its students. If wonder is recast as curiosity—a ‘skill’ that leads reliably to the ‘right answer’—students will inevitably find quicker, more efficient means to arrive at the required information. Religious education is uniquely equipped to supplement inquisitive curiosity with a more contemplative wonder that eschews easy answers. In doing so, it would equip students to grapple with what modern society has become so adept at evading: the “stubborn there-ness” (Arendt in Medina J, Wood D (eds) Truth: engagements across philosophical traditions. Blackwell Publishing, London, 2005, p. 310) of mystery that characterizes the most meaningful questions of our existence.